GAMBARAN PELAKSANAAN PENINGKATAN PROGRAM PARTISIPASI PRIA DALAM KB MOPDI BONDOWOSO (STUDI KASUS DI KECAMATAN MAESAN) - Susilawati Susilawati (Fakultas Kesehatan Masyarakat, Universitas Jember, 2012)
Paradigm shift from control and family planning programs into fertility decline approach towards reproductive health and gender equality in Indonesia has not provedthe participation of men in family planning by 4.4% SDKI 2007. This is in contrast with the achievement of family planning of vasectomy in Bondowoso that has been the highest in East Java (2005-2009). This study is a qualitative study with a case study approach. The data were collected with a indepth interview and FGD to the managers of family planning at subdistrict Maesan. Informants in this study were as many as 45 people. The analysis of the data in this study used thematic content analysis method. These results illustrate that the implementation of the program participation Program Planning Vasectomy at subdistrict Maesan done by involving a key person as a participant vasectomy and as a motivator and help them find the target potential participants because they can explain vasectomy appropriately with their appropriate experience. Keywords: Participation, vasectomy, family planning programs